WORLD OF WARCRAFT AS LEISURE: SOCIABILITY AND CONFLICT IN CYBERSPACE. - Reis, Leoncio José de Almeida; Cavichiolli, Fernando Renato (Movimento, 2014)
World of Warcraft is a digital game very well-known and played worldwide. In the virtual world of the game, thousands of people connected to the internet come together to interact, relate and share the experience of playing. This text is a summary of the main findings of ethnographic research that addressed the gameas a practical leisure and from the perspective of the players. Among the main topics discussed are issues related to performance, competition, sociability and violence.